Managing Archaeological Landscapes in Northumberland Till Tweed Studies Volume 1 - Passmore, D. G. (Historic England, 2009)
The Till-Tweed river catchment areas in Northumberland contain outstanding archaeological and palaeoenvironmental remains which have been in general only poorly understood. This study has assembled detailed data that will provide a platform for future landscape-based research and site-based investigation. Written from a landscape, or geoarchaeological perspective, this study develops a methodology and management tool that will allow planners, curators and developers working in the region to to easily access information across sectors, and provide a transparent and easily comprehended record of sensitive archaeological and palaeoenvironmental sites.